What I know, what I want to know, what I learned: Activating EFL college students' cognitive, behavioral, and emotional engagement through structured feedback in an online environment - Al-Obaydi, Liqaa Habeb; Shakki, Farzaneh; Tawafak, Ragad M.; Pikhart, Marcel; Ugla, Raed Latif (Frontiers in Psychology, 2023)
Given the spread of Covid-19 pandemic, online classes have received special attention around the world. Since teachers have a lasting effect on the students, the teacher-student relationship is a pivotal factor in language learning classes. Students won't be engaged in class activities if they are not sufficiently challenged by them or if they do not find them interesting, especially in online classes. From this point of view, motivating, engaging and testing techniques in online classes are of high importance. The present study attempts to demonstrate a kind of correlation between structured feedback and three types of engagement, namely cognitive, behavioral, and emotional engagement in an online class. The structured feedback which is used at the end of each lesson lets the students express what they know, what they want to know, and what they learned. The sample of the study consists of 114 EFL third-year college students. The findings of the study reveal that there are positive and significant correlations between the three types of engagement; cognitive, behavioral, and emotional, and the use of structured feedback in online classes. In a nutshell, some academic implications and recommendations are provided.